Associated factors with musculoskeletal pain in nursing students - Bruna Xavier Morais; Tânia Solange Bosi de Souza Magnago; Graziela Maria Rosa Cauduro; Graziele de Lima Dalmolin; Cecília Mariane Pinheiro Pedro; Naiane Glaciele da Costa Gonçalves (Universidade Federal de Santa Maria, 2017)
Aim: to verify the prevalence and factors associated with musculoskeletal pain in Nursing students. Method: cross-sectional study performed in 2014 with 149 Nursing students in a public University in the southern region of Brazil. A questionnaire with sociodemographic, health and academic questions was used as well as the Brazilian version of the Standardized Nordic Questionnaire. The association was estimated by the Odds Ratio and its confidence intervals. Results: in the last seven days, musculoskeletal pain in the lower back (61,1%) and neck area (54,4%) prevailed. Associations between pain in the region of the neck with consuming alcoholic beverages (OR=2,84; IC95%=1,28-6,29), in legs with performing academic experiences (OR=2,03; IC95%=1,05-4,00), and in shoulders with not doing physical activity (OR=2,13; IC95%=1,01-4,45) and not having time for entertainment (OR=2,08; IC95%=1,03-4,22) were observed. Conclusions: because of the high percentage of musculoskeletal pain, it is necessary to take measures to prevent this problem still in the academy